Durable response to anti-PD-1 immunotherapy in epithelioid angiomyolipoma: a report on the successful treatment of a rare malignancy. Issue 1 (1st October 2018) - Lattanzi, Michael; Deng, Fang-Ming; Chiriboga, Luis A.; Femia, Alisa N.; Meehan, Shane A.; Iyer, Gopa; Voss, Martin H.; Sundatova, Yuliya; Huang, William C.; Balar, Arjun V.
Abstract : Background: Malignant angiomyolipoma is an uncommon tumor of the class of perivasciular epithelioid cell neoplasms (PEComas). These tumors are characteristically driven by deleterious mutations in the tumor suppressors TSC1 and TSC2, whose gene products typically act to inhibit mTOR. There are several cases of malignant angiomyolipoma which exhibit transient responses to mTOR inhibitors, forming the basis of current practice guidelines in malignant PEComa. However the tumors ultimately acquire resistance, and there is no well-established second-line option. Despite the increasing prevalence of immunotherapy across a wide range of solid tumors, little is known about the immune infiltrate and PD-L1 expression of angiomyolipoma. Furthermore, there is no reported case on the treatment of malignant angiomyolipoma with an immune checkpoint inhibitor. Case presentation: A 38 year-old man presented with gross hematuria and was diagnosed with renal epithelioid angiomyolipoma. Despite surgical resection, the tumor recurred and metastasized. Targeted genomic sequencing revealed a deleterious mutation in TSC2, and the patient was treated with the mTOR inihbitor everolimus. The patient went on to have a partial response but ultimately progressed. He was then treated with the anti-PD-1 immune checkpoint inhibitor nivolumab, and achieved a durable near-complete response which is ongoing after two years of treatment. Immunohistochemical staining of tumor tissue revealed strong PD-L1 expression and a brisk T-cell infiltrate. Conclusions: We report on the first durable systemic treatment of malignant epithelioid angiomyolipoima with the use of PD-1 antibody nivolumab. Given the absence of prospective clinical trials in this exceedingly rare disease, particularly in the second-line setting, immune checkpoint inhibitors like nivolumab should be considered.